2020
DOI: 10.1016/j.jsat.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monthly buprenorphine extended-release injections on patient-centered outcomes: A long-term study

Abstract: The physical, social, psychological, and economic burden of opioid use disorder (OUD) is substantial. As of the year 2019, the predominant focus of OUD research was outcomes such as retention and abstinence. We report herein the effects of extended-release buprenorphine (BUP-XR), the first FDA-approved subcutaneously injected, monthly treatment for OUD, on patient-centered outcomes. Materials and methods: Patient-centered outcomes were collected during an open-label safety study of participants with OUD (NCT# … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 19 publications
0
49
0
Order By: Relevance
“…In the general population, patients receiving buprenorphine extended-release report higher treatment satisfaction, and the medication leads to greater positive, patient-centered outcomes. 41 These benefits are particularly important in the postpartum period, a challenging time in a woman's life with drug overdoses being a leading cause of death. 42 Use of buprenorphine extended-release, however, requires that patients have a history of receiving the immediate-release formulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, patients receiving buprenorphine extended-release report higher treatment satisfaction, and the medication leads to greater positive, patient-centered outcomes. 41 These benefits are particularly important in the postpartum period, a challenging time in a woman's life with drug overdoses being a leading cause of death. 42 Use of buprenorphine extended-release, however, requires that patients have a history of receiving the immediate-release formulation.…”
Section: Discussionmentioning
confidence: 99%
“…50 Furthermore a community study showed that LAIB had high satisfaction (88%) and a 7% increase in employment rates. 17…”
Section: Long-acting Injectable Buprenorphinementioning
confidence: 99%
“…3,16 In 2019, long-acting injectable buprenorphine (LAIB) became available in Australia and may alleviate some of the difficulties of long-term treatment. 17,18 Injections given weekly or monthly, could reduce the demand on GPs and pharmacies and could improve quality of life by negating the need to attend a pharmacy frequently for supervised dosing of buprenorphine. 17 Opioid withdrawal has historically been neglected in EDs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations